2020
DOI: 10.3390/plants9121650
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral, Antioxidant, and Antihemolytic Effect of Annona muricata L. Leaves Extracts

Abstract: Annona muricata L. is a tropical tree that is used in traditional medicine around the world. The high content of flavonoid, alkaloid, acetogenin, phenolic and lipophilic compounds of this tropical tree forms the basis of its traditional medical uses. Our objective was to study soursop leaf extracts to support their use as antiviral therapies and investigate their protective effects against oxidative damage. The aqueous extract (AE) and acidified ethanolic extract (AEE) of soursop leaves were characterized by u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 32 publications
1
16
0
1
Order By: Relevance
“…Another study showed that acidified ethanolic extract of A. muricata decreased viral replication after 1 h of contact time. This activity may be due to the presence of phenolic compounds such as rutin [93]. Acetogenins such as annomuricin a, annomuricin b, annomuricin c, muricatocin c, muricatacin, cis-annonacin, annonacin-10-one, cis-goniothalamicin, arianacin, and javoricin were shown to possess good inhibitory activity against SARS-CoV-2 spike proteins (in silico).…”
Section: Antiviralmentioning
confidence: 99%
“…Another study showed that acidified ethanolic extract of A. muricata decreased viral replication after 1 h of contact time. This activity may be due to the presence of phenolic compounds such as rutin [93]. Acetogenins such as annomuricin a, annomuricin b, annomuricin c, muricatocin c, muricatacin, cis-annonacin, annonacin-10-one, cis-goniothalamicin, arianacin, and javoricin were shown to possess good inhibitory activity against SARS-CoV-2 spike proteins (in silico).…”
Section: Antiviralmentioning
confidence: 99%
“…The leaves [ 96 , 97 , 98 , 99 , 100 ], pericarp [ 36 , 101 ], fruits [ 34 , 102 ], seeds [ 36 , 103 ], and roots [ 35 ] of A. muricata have ethnomedical uses. Roots of A. muricata have been employed in herbal therapy, whereas stem barks, stems, seeds, and leaves are the most common constituents in traditional medicinal decoctions [ 104 , 105 , 106 ].…”
Section: Ethnomedicinal Usesmentioning
confidence: 99%
“…Using the LC-MS/MS technique, Kim et al found the flavonoids kaempferol-3- O -rutinoside and quercetin-3- O -rutinoside in a graviola leaf extract, in addition to demonstrating the ability of soursop leaves to boost immunity [ 75 ]. Similarly, Balderrama-Carmona et al identified rutin as the predominant compound through analyses performed using the UPLC technique, and reported that graviola leaves can help reduce oxidative stress in human erythrocytes, as well as viral infections [ 78 ]. Thus, it is possible to observe that, regardless of the technique used, rutin, kaempferol, quercetin, and their derivatives are prominently present in A. muricata .…”
Section: Resultsmentioning
confidence: 99%